1990
DOI: 10.1093/oxfordjournals.eurheartj.a059628
|View full text |Cite
|
Sign up to set email alerts
|

Felodipine in chronic stable angina: a randomized, double-blind, placebo-controlled, crossover study

Abstract: To investigate the antianginal efficacy and tolerability of felodipine, a new dihydropyridine calcium antagonist, 20 patients with stable exertional angina, not completely controlled by beta-blocker monotherapy, entered a randomized, double-blind, placebo-controlled, crossover study. Patients on standard beta-blocker therapy, who had at least 3 weekly anginal episodes and a reproducible exercise test (stopped for angina and ECG signs of ischaemia) at the end of 2 weeks placebo treatment, were eligible for the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(4 citation statements)
references
References 0 publications
0
4
0
Order By: Relevance
“…There were 28 studies (37 comparisons) of a CCB added to a BB ( n = 2468); 7–35 12 studies (12 comparisons) of a BB added to a CCB ( n = 1489); 9,11,12,1416,19,20,24,25,29,34 7 studies (8 comparisons) of a LAN added to a BB or CCB ( n = 329); 7,3640 3 studies (4 comparisons) of ranolazine added to a BB or CCB ( n = 1388); 41–43 8 studies (9 comparisons) of trimetazidine added to a BB or CCB ( n = 2875); 4451 1 study of ivabradine added to a BB ( n = 889). 52 No studies were found that evaluated the impact of nicorandil in an add-in role on either ETT or clinical measures of anti-anginal efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…There were 28 studies (37 comparisons) of a CCB added to a BB ( n = 2468); 7–35 12 studies (12 comparisons) of a BB added to a CCB ( n = 1489); 9,11,12,1416,19,20,24,25,29,34 7 studies (8 comparisons) of a LAN added to a BB or CCB ( n = 329); 7,3640 3 studies (4 comparisons) of ranolazine added to a BB or CCB ( n = 1388); 41–43 8 studies (9 comparisons) of trimetazidine added to a BB or CCB ( n = 2875); 4451 1 study of ivabradine added to a BB ( n = 889). 52 No studies were found that evaluated the impact of nicorandil in an add-in role on either ETT or clinical measures of anti-anginal efficacy.…”
Section: Resultsmentioning
confidence: 99%
“…The coronary blood flow increased as a consequence of dilation of both coronary resistance vessels and epicardial coronary arteries (33). A preliminary clinical program in patients with exertional angina showed that felodipine exerts antianginal effects both in monotherapy and in combination with a P-blocker (14, 75,97,99,110). The duration of these studies ranged from 1 day to 4 weeks and exercise tolerance increased by 10-60% and the anginal attack rate and consumption of nitroglycerin were reduced.…”
Section: Safety Of Felodipine In Patients With Diseases Commonly Compmentioning
confidence: 99%
“…The number of patients with chest pain during exercise was significantly reduced and, in those patients who had early onset chest pain (<6 min) at baseline exercise testing, there was a significant increase in the time to chest pain in the amlodipine group. There are numerous other smaller randomised trials which have also shown no advantage in combining dihydropyridines and beta‐blockers 20‐22 …”
Section: Discussionmentioning
confidence: 99%